2005
DOI: 10.1002/bsl.677
|View full text |Cite
|
Sign up to set email alerts
|

Gender and psychopathy: an overview of important issues and introduction to the special issue

Abstract: One of the most important concepts to ever emerge in forensic psychology and law is psychopathy. It would be difficult to exaggerate the profound effect the construct has had on research and practice in correctional psychology, psychiatry, and criminology. Much less pronounced has been an interest in understanding the potential relevance and practical implications that this personality disorder might have for providing insights into antisocial behaviors and crimes committed by girls and women. In this paper we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 64 publications
3
62
0
1
Order By: Relevance
“…Furthermore, these biases were specific of the affective-interpersonal dimension of psychopathy, strengthening the views that the two dimensions of psychopathy make distinct contributions to emotional and moral processing; and that while psychopathy might be manifested differently in females and males, either due to gender-role socialization or biological differences (e.g. Nicholls & Petrila, 2005), its central characteristics appear to be similar. Future work with larger samples from community and forensic settings should further probe the generalizability of these important preliminary findings and the precise extent to which different components of psychopathy present distinct associations with particular empathic and moral processes.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Furthermore, these biases were specific of the affective-interpersonal dimension of psychopathy, strengthening the views that the two dimensions of psychopathy make distinct contributions to emotional and moral processing; and that while psychopathy might be manifested differently in females and males, either due to gender-role socialization or biological differences (e.g. Nicholls & Petrila, 2005), its central characteristics appear to be similar. Future work with larger samples from community and forensic settings should further probe the generalizability of these important preliminary findings and the precise extent to which different components of psychopathy present distinct associations with particular empathic and moral processes.…”
Section: Discussionsupporting
confidence: 54%
“…Research so far indicates that emotional and personality correlates of psychopathy such as glibness, grandiosity, lack of empathic concern are akin across genders, but similarities in behavioural correlates, such as criminal behaviour and type of aggression, seem to be less consistent (see Verona & Vitale, 2006, for a review). It has been suggested that differences found across genders are mainly differential expressions of the same underlying construct (Nicholls & Petrila, 2005), and that the same personality traits may confer risk for different forms of behaviour for women versus men (Verona, Sprague, & Javdani, 2012). …”
Section: Dimensions Of Psychopathic Personalitymentioning
confidence: 99%
See 1 more Smart Citation
“…A literatura geral é bastante consistente relativamente ao facto de os comportamentos antissociais, delinquentes ou agressivos terem frequentemente uma estrutura de personalidade psicopática como correlata (e.g., Edens, Guy, & Fernandez, 2003;Farrington, 2005;Loney, Frick, Clements, Ellis, & Kerlin, 2003;Nicholls & Petrila, 2005;Robinson, 2005;Seagrave & Grisso, 2002), mas a literatura sobre diferenças entre sexos na delinquência com que se possam contrastar estes achados não abunda. Ainda assim, a investigação existente é sugestiva de uma estrutura de personalidade com traços mais marcados de psicopatia no sexo masculino (e.g., Campbell, Porter, & Santor, 2004;Marsee, Silverthorn, & Frick, 2005;Penney & Moretti, 2007;Strand & Belfrage, 2005;Ugueto, 2005), embora noutros estudos (e.g., Vaughn, 2005) também não se tenham encontrado diferenças entre sexos nos resultados do APSD.…”
Section: Discussão E Conclusãounclassified
“…Violence is a solution that is available to them as other forms to control someone such as deceit, manipulation, and charming someone. Female psychopaths were comparable to psychopathic males in terms of irresponsible lifestyles (Rogers, Jordan, & Harrison, 2007), higher unemployment rates and relationship instability (Salekin et al, 1998) more promiscuous behavior (Grann, 2000) and relying on manipulation to achieve goals (Nicholls & Petrila, 2005). Regardless of gender, they do not value traditional social norms, close relationships, can be vengeful, physically violent, and victimize others for personal gain (O'Connor, 2002).…”
Section: Female Behavioral Traitsmentioning
confidence: 99%